2017
DOI: 10.1002/path.4979
|View full text |Cite
|
Sign up to set email alerts
|

Airway remodelling and inflammation in asthma are dependent on the extracellular matrix protein fibulin-1c

Abstract: Asthma is a chronic inflammatory disease of the airways. It is characterized by allergic airway inflammation, airway remodelling, and airway hyperresponsiveness (AHR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 68 publications
(101 reference statements)
0
85
0
1
Order By: Relevance
“…Airway remodeling occurs in patients with asthma, in particular those with chronic or severe asthma (Liu et al, ). Airway remodeling is associated with the accumulation of ECM proteins, such as collagens and fibronectin (Liu et al, ). In the present study, the mRNA and protein levels of collagen type I and fibronectin were detected by qRT‐PCR and western blot, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Airway remodeling occurs in patients with asthma, in particular those with chronic or severe asthma (Liu et al, ). Airway remodeling is associated with the accumulation of ECM proteins, such as collagens and fibronectin (Liu et al, ). In the present study, the mRNA and protein levels of collagen type I and fibronectin were detected by qRT‐PCR and western blot, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of mucus secretion may contribute to the treatment of asthma. Airway remodeling and inflammation in asthma are dependent on the ECM proteins, such as collagens and fibronectin (Liu et al, ). However, airway remodeling with excessive deposition of ECM is correlated with increased airway responsiveness and asthma severity (Goldstein, Lauer, Caplan, & Bonfield, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muc7, Muc13, Muc15, and Muc19 gene and protein expression is facilitated by several cytokines, including TNF-α and IL-1β, secreted by macrophages [8,34]. In previous reported that IL-6, IL-8, and TNF-α secreted by lung lymphocytes specifically induce the secretion of Muc7, Muc13, Muc15, and Muc19 to promote destruction of lung tissue [35,36]. Muc7, Muc13, Muc15, and Muc19, IL-1β, and TNF-α expression levels in response to infection were significantly reduced in A549 cells transformed with siRNA targeting IKK-α and IKK-β.…”
Section: Discussionmentioning
confidence: 99%
“…The area of collagen deposition (lm 2 ), airway epithelial area (lm 2 ) and cell (nuclei) number were assessed in a minimum of four small airways (basement membrane [BM] perimeter < 1000 lm) per section. Data were normalised to BM perimeter (lm) and quantified using ImageJ software (Version 1.49h; National Institutes of Health, New York City, NY, USA) 19,21,24,80 .…”
Section: Airway Remodellingmentioning
confidence: 99%